Structure of the Andean Palaeozoic basement in the Chilean coast at 31º 30’ S: Geodynamic evolution of a subduction margin - García-Sansegundo, J.; Farias, P.; Heredia, N.; Gallastegui, G.; Charrier, R.; Rubio-Ordóñez, A.; Cuesta, A. (Journal of Iberian Geology, 2014)
The Palaeozoic basement outcropping to the north of Los Vilos is formed by (i) the Choapa Metamorphic Complex (ChMC) made of metabasites (amphibolites and retrogressed eclogites), fine-grained gneisses, schists and quartz-schists, and (ii) the meta-sedimentary and sedimentary rocks of the Arrayán and Huentelauquén formations respectively. Near Huentelauquén (31º 30’ S), the ChMC has been affected by three deformation episodes related with the Gondwanan orogenic episode. The first episode (D1) is represented by a foliation (S1) formed under HP-LT metamorphic conditions and preserved in syn-D2 garnet and albite porphyroblasts. A generalised crenulation cleavage (S2) was developed under pressure decreasing conditions during the second deformation episode (D2). This episode is responsible for the exhumation of the ChMC, which took place through an east-directed reverse fault system that thrusts the ChMC over the Arrayán Formation, producing more than 20 km shortening. The third deformation episode (D3) is represented by a west-verging kilometre-scale anticline, with a thrust in its reverse limb (Las Caldas thrust). Minor folds and crenulations are also associated with D3. D3 structures affect the ChMC and the Arrayán Formation and are responsible for the overturning of the D2 thrusts. The Huentelauquén Formation, late Carboniferous – Permian in age, is the latest unit deformed by Gondwanan structures. The characterisation of the structure and its relation to metamorphism in the study area, lead to propose a geodynamic model related with an Andean type non-collisional orogenic process, for the Gondwanan orogenic episode of the Andes at this latitude.